Tracked Changes. Ships and marine technology. Service personnel for the maintenance, thorough examination, operational testing, overhaul and repair of lifeboats and rescue boats, launching appliances and release gear. Level 1 technical training Part 3, (18th October 2022) - British Standards Institution,
No abstract available